2018
DOI: 10.1080/0142159x.2017.1394576
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds and interpretations: How clinical competency committees identify pediatric residents with performance concerns

Abstract: Identifying residents with performance concerns is important for their education and the care they provide. This study delineates strategies used by CCC members across several programs for identifying these residents, which may be helpful for other CCCs to consider in their efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…rotation ratings, faculty comments, personal experience with residents) 31 and investigating how CC members identified residents with performance concerns. 32 We believe that this work is complemented by our own, which pragmatically focused on determining what information CCs need and how it can be provided effectively. Further, our work has contributed to the literature by providing a thematic framework outlining CC needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rotation ratings, faculty comments, personal experience with residents) 31 and investigating how CC members identified residents with performance concerns. 32 We believe that this work is complemented by our own, which pragmatically focused on determining what information CCs need and how it can be provided effectively. Further, our work has contributed to the literature by providing a thematic framework outlining CC needs.…”
Section: Discussionmentioning
confidence: 99%
“…BT reviewed the literature on CC function, 11,16,[31][32][33] learning analytics, 12,21 and data visualization. 18,22,23,27,34 He summarized this work for our team's programming experts (DJ and VK) to provide the context required to support dashboard programming.…”
Section: Phase 1 Analysis and Explorationmentioning
confidence: 99%
“…3 Yet studies have suggested that CCCs infrequently use clinical performance data or patient experience survey data as a source of assessment. 4,5 All CCCs should look for opportunities to seek out and include this data, as it is essential for judging competency in communication skills, quality improvement, patient safety, and systems thinking.…”
mentioning
confidence: 99%
“…Invite residents to perform selfassessments with the milestones, discuss the differences between the CCC and resident assessment, and jointly create a learning plan. Share resources for CCCs and milestones (available from Accreditation Council for Graduate Medical Education International and others) with faculty and residents 4…”
mentioning
confidence: 99%
See 1 more Smart Citation